2018
DOI: 10.1111/jace.16205
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion mechanism of lightweight microporous alumina‐based refractory by molten steel

Abstract: Lightweight refractory linings for industrial furnaces have become important subjects of development in high‐temperature industries. The reaction mechanism between a lightweight microporous alumina‐based refractory material and molten steel was investigated in this study. The main mechanism of refractory damage was structural spalling, caused by steel penetrating the pores. The many micropores in lightweight microporous alumina have high specific surface area and reactivity, inducing the formation of FeO–Fe2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…With the dissolution of magnesia grains, the curvature radius of magnesia grains changes; it can be calculated using the Gibbs‐Thompson Equations :Csp-CflCfl=2γs,lVnormalMRT+273rnormalswhere C sp is the surface saturation solubility (ie, C s ), wt%; C fl is the plane saturation solubility, wt%; V M is the molar volume, m 3 /mol; γ s,l is the interfacial tension (energy), N/m; R is the gas constant, 8.314 J/(mol·K); T is the temperature, °C; and r s is the radius of curvature (radius of magnesia grains), μm. Therefore, the saturation solubility of the particle interface is higher than that of slag, which leads to the dissolution of magnesia aggregates in molten slag.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…With the dissolution of magnesia grains, the curvature radius of magnesia grains changes; it can be calculated using the Gibbs‐Thompson Equations :Csp-CflCfl=2γs,lVnormalMRT+273rnormalswhere C sp is the surface saturation solubility (ie, C s ), wt%; C fl is the plane saturation solubility, wt%; V M is the molar volume, m 3 /mol; γ s,l is the interfacial tension (energy), N/m; R is the gas constant, 8.314 J/(mol·K); T is the temperature, °C; and r s is the radius of curvature (radius of magnesia grains), μm. Therefore, the saturation solubility of the particle interface is higher than that of slag, which leads to the dissolution of magnesia aggregates in molten slag.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…To mitigate the heat loss, microporous aggregates were used to prepare the lightweight refractories for working linings, instead of dense aggregates. [8][9][10][11][12][13][14] The previous study indicated that lightweight magnesia-based refractories have higher strengths and lower thermal conductivity than dense refractories. 15 Mechanical properties and fracture behavior of lightweight magnesia-based refractories have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…As generally known, the alumina based refractories are important and conventional refractories have been widely used as wear lining in steel ladle, nozzle, slide plate, and other metallurgical equipments. 23,24 The regular alumina based refractories contain Al 2 O 3 -MgO, Al 2 O 3 -C, Al 2 O 3 -SiO 2, and Al 2 O 3 -ZrO 2 , et al 25 However, numerous other patterns of corrosion or erosion of the refractory, such as pin-holes, necking, waist formation, and cut formation, at the phase interface have been reported. 5 The shape of the attack profile mainly depends on the compositions of the refractory and molten phase.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we recently observed a quasi‐volcanic corrosion with a macro‐scale continuous peak pattern at the alumina refractory – slag – air interface, which has not been observed in previous studies. As generally known, the alumina based refractories are important and conventional refractories have been widely used as wear lining in steel ladle, nozzle, slide plate, and other metallurgical equipments 23,24 . The regular alumina based refractories contain Al 2 O 3 ‐MgO, Al 2 O 3 ‐C, Al 2 O 3 ‐SiO 2, and Al 2 O 3 ‐ZrO 2 , et al 25 However, numerous other patterns of corrosion or erosion of the refractory, such as pin‐holes, necking, waist formation, and cut formation, at the phase interface have been reported 5 .…”
Section: Introductionmentioning
confidence: 99%